2017
DOI: 10.1186/s13063-017-2027-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combining manual therapy with exercise for mild chronic obstructive pulmonary disease: study protocol for a randomised controlled trial

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a major cause of disability and hospital admission. Current management strategies have not been successful in altering the loss of lung function typically seen as the disease progresses. A recent systematic review into the use of spinal manipulative therapy (SMT) in the management of COPD concluded that there was low level evidence to support the view that a combination of SMT and exercise had the potential to improve lung function more than exercise al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Many studies have shown the positive effect of respiratory gymnastics [10,14,17,19] and physical training [1,3,9] on the indicators of external respiration function, namely the increase in forced expiratory volume in 1 second. The results of several randomized controlled studies have revealed that the use of manual therapy with physical training helps to improve physical performance [5,20]. Some papers provide research results related to the application of Nordic walking [2,6,21], which can be a useful practice for normalizing the work of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown the positive effect of respiratory gymnastics [10,14,17,19] and physical training [1,3,9] on the indicators of external respiration function, namely the increase in forced expiratory volume in 1 second. The results of several randomized controlled studies have revealed that the use of manual therapy with physical training helps to improve physical performance [5,20]. Some papers provide research results related to the application of Nordic walking [2,6,21], which can be a useful practice for normalizing the work of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Given the active work of the entire body while walking, the respiratory volume of the lungs increases by about 30%. To date, it has been proven that this progressive walking is 46% more effective than normal walking or jogging and contributes to the normalization of vascular tone [5,8]. CG patients passed a distance of 1500-2500 meters per day on a flat terrain, with a breathing rhythm of inhalation in 2-3 steps and exhalation in 5-6 steps.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in the prehospital setting are often in a state of distress, and may not be able to provide informed consent for research participation [61]. Additionally, there may be situations where informed consent cannot be obtained in a timely manner due to the patient's condition or the urgency of the situation [62]. In such cases, alternative methods of obtaining informed consent, such as deferred or waived consent, may need to be considered [63].…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Candemir et al 3 evaluated the relationship between the COPD assessment test and improvements after PR and PR efficiency in subjects with COPD. Engel et al 4 designed a randomized controlled trial (RCT) to investigate whether the combination of exercise and manual therapy including spinal manipulative therapy produced sustainable improvements in lung function and exercise capacity in 202 subjects with stable mild COPD.…”
Section: Introductionmentioning
confidence: 99%